2009
DOI: 10.1167/iovs.08-2247
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofChlamydia trachomatisOcular Infection in Trachoma-Endemic Communities by rRNA Amplification

Abstract: The rRNA-based test appears to have significantly greater sensitivity than PCR for the detection of ocular C. trachomatis infection in children in trachoma-endemic villages. The increased sensitivity of the rRNA-based test may be due to its ability to detect low levels of C. trachomatis infection in individuals, which can occur especially after antibiotic treatment. Data from past studies in which PCR was used to assess the prevalence of infectious trachoma after community-wide antibiotic treatments could have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…No manufacturer has sought FDA clearance with respect to detecting C. trachomatis in ocular samples. However, past experience has indicated that nucleic acid amplification tests (NAATs) perform very well when analyzing ocular samples, especially NAATs designed to detect rRNA (9). This study demonstrated that m2000 and GeneXpert performed with great accuracy when detecting C. trachomatis in ocular samples, indicating that either assay could be utilized for future trachoma studies.…”
mentioning
confidence: 88%
“…No manufacturer has sought FDA clearance with respect to detecting C. trachomatis in ocular samples. However, past experience has indicated that nucleic acid amplification tests (NAATs) perform very well when analyzing ocular samples, especially NAATs designed to detect rRNA (9). This study demonstrated that m2000 and GeneXpert performed with great accuracy when detecting C. trachomatis in ocular samples, indicating that either assay could be utilized for future trachoma studies.…”
mentioning
confidence: 88%
“…Existing nucleic acid amplification tests, considered a gold standard for a laboratory test of infection [11], [12], [13], involves instrumentation that is expensive and requires developed laboratories not widely available in many trachoma endemic countries. Thus, there is a need for a simple, inexpensive rapid test for CT that can be performed in the field in trachoma endemic areas.…”
Section: Introductionmentioning
confidence: 99%
“…Among most frequent extragenital manifestations of C. trachomatis are sexually acquired reactive arthritis (SARA), conjunctivitis and perihepatitis [1]. In most of the cases of ophthalmological manifestations C. trachomatis can be detected and/or isolated in the eye swabs [2]. It is believed that immunological and hormonal phenotype as well as some genotype characteristics, particularly expression of human leucocyte antigen B27, predetermine the severity of extragenital manifestations caused by C. trachomatis [3].…”
Section: Introductionmentioning
confidence: 99%